Seismic behavior of composite columns with steel reinforced ECC permanent formwork and infilled concrete. (1st June 2020) - Pan, Zuanfeng; Zhu, Yazhi; Qiao, Zhi; Meng, Shaoping
Highlights: A new kind of reinforced engineered cementitious composite columns is developed. The new column is characterized by the use of ECC as the permanent formwork. Seismic behavior of the composite column is examined by experimental program. Numerical modeling is performed to study the effects of column design parameters. Abstract: This paper presented a new kind of steel-reinforced engineered cementitious composite (RECC/C) columns, which consisted of a permanent formwork fabricated by the steel-reinforced ECC (RECC) and plain concrete infilled within the RECC formwork. The main objective of this paper was to examine the seismic behavior of the RECC/C columns through experimental and numerical approaches. Six RECC/C composite columns and a corresponding conventional reinforced concrete (RC) column specimen were prepared for the experimental investigations. The test results revealed that the RECC/C composite columns had better shear capacity, energy dissipation capacity, and a higher ductility as compared to the RC column. An increase in the transverse reinforcement, shear-span ratio, or a decrease in the axial compression resulted in the improvement of the ductility and energy dissipation capacity of the RECC/C columns. Numerical modeling of the RECC/C column was carried out based on OpenSees. The parametric studies offered insights into the effects of the longitudinal reinforcement, shear-span ratio, axial compression, ECC compressive strength and ultimate compressive strain, and the thickness of ECC layer/formwork on the flexural behavior of the RECC/C columns. The results showed that an increase in each of those ECC material parameters may be beneficial for the member ductility. An appropriate thickness of the ECC layer was crucial to the flexural behavior of the proposed composite columns.